Skater`s dilemma - Ichinose, G.; Miyagawa, D.; Ito, J.; Masuda, N. (Department of Mathematical and Systems Engineering, Shizuoka University, 2020)
In some athletic races, such as cycling and types of speed skating races, athletes have to complete a relativelylong distance at a high speed in the presence of direct opponents. To win such a race, athletes are motivatedto hide behind others to suppress energy consumption before a final moment of the race. This situation seemsto produce a social dilemma: players want to hide behind others, whereas if a group of players attempts to doso, they may all lose to other players that overtake them. To support that speed skaters are involved in sucha social dilemma, we analyzed video footage data for 14 mass start skating races to find that skaters that hidbehind others to avoid air resistance for a long time before the finallap tended to win. Furthermore, the finishrank of the skaters in mass start races was independent of the record of the same skaters in time-trial racesmeasured in the absence of direct opponents. The results suggest that how to strategically cope with askater`sdilemmamay be a key determinant for winning long-distance and high-speed races with direct opponents.